The effectiveness of the STAD Cooperative Learning Method assisted by Flashcard Media in improving students’ learning outcomes - Yoan Alfarezy Indra; Febri Prasetya; Primawati Primawati; Zainal Abadi (Researcher and Lecturer Society, 2025)
This study explores the effectiveness of the Student Teams Achievement Divisions (STAD) cooperative learning model, supported by flashcard media, in enhancing student learning outcomes in Manufacturing Technical Drawing at SMK Negeri 1 West Sumatra. A quasi-experimental control group design was employed, where the experimental group used the STAD method integrated with flashcards, and the control group received traditional lecture-based instruction. Post-test results showed that the experimental group significantly outperformed the control group, achieving a higher mean score of 79.68 compared to 63.84, with an N-Gain score of 50.81%, indicating moderate improvement. The study found that the STAD model, combined with flashcards, boosted academic achievement and promoted more consistent and equitable learning outcomes. Flashcards played a vital role by simplifying complex concepts and enhancing student engagement. This study fills a gap in vocational education by demonstrating the effectiveness of combining cooperative learning and visual aids in technical education. The research offers valuable insights for educators in similar contexts, proposing a cost-effective and scalable instructional method that can be applied across various technical disciplines. However, the study’s limitation lies in its short-term implementation, and further research is needed to explore the long-term effects of this combined learning strategy.